Immunoglobulin production of human lymphocytes stimulated by Staphylococcus aureus Cowan I and pokeweed mitogen: differential effects of recombinant interleukin-2. - Pryjma, J (1986)
The number of immunoglobulin-secreting cells (ISC) upon stimulation with pokeweed mitogen (PWM) or Staphylococcus aureus Cowan I (SAC) in recombinant interleukin-2 (rIL-2)-supplemented cultures of human peripheral blood mononuclear cells (PBMC) and co-cultures of B and T cells was studied. It has been shown that the addition of rIL-2 to culture can enhance or depress the number of ISC depending on the polyclonal B-cell activator used for culture stimulation. The SAC-induced response was enhanced in the presence of rIL-2, while the number of ISC in PWM-stimulated cultures was depressed. Moreover, in cultures stimulated simultaneously by both activators, the suppressive effect of rIL-2 prevailed, indicating that the reported direct effect of the lymphokine on SAC-activated B cells cannot overcome the suppressive activity of PWM-induced suppressor T cells. rIL-2 could not activate suppressor T cells in the absence of PWM, and has no effect on the number of helper or suppressor cells in the culture.